Consequences of Coronavirus as a Predictor of Emotional Security among Mothers of Children with Intellectual Disabilities - Abuzaid, Suad M.O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Parents of children with intellectual disability (ID) suffer from comparatively emotional insecurity compared to parents of children without ID, especially during periods of crisis, such as the outbreak of coronavirus pandemic. This study aimed to investigate the consequences of Coronavirus as a predictor of emotional security among mothers of children with intellectual disabilities. Mothers of children with intellectual disabilities were considered for data collection. The study group of the research consists of 120 mothers who have children with intellectual disabilities. They aged 23-55 years, (M= 43.23, SE=0.075). Consequences of Coronavirus Questionnaire (CCQ-20) and Emotional Security Scale (ESS-20) were used to collect and analyze data. For this study, quantitative survey research was employed. The independent variable is the consequences of Coronavirus, and emotional security is the dependent variable. The independent variable is the consequences of Coronavirus, and emotional security is the dependent variable. To test the hypotheses of the study, Pearson correlation and Linear regression analysis were conducted. Findings indicate that the independent variable (Coronavirus) contributed to the prediction of emotional security among mothers of children with intellectual disabilities. Findings of the current study indicate that the greater the Consequences of Corona, the less emotionally secure the mother is likely to feel during the COVID-19 lockdown in Saudi Arabia.